2017
DOI: 10.1111/ap.12268
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Professional Competency Problems in Clinical Psychology Trainees

Abstract: Objective: Clinical psychology trainees with problems of professional competence (PPC) continue to be a challenge for courses. Despite the rapid development of competency-based training models, the impact of this shift to the identification and management of professional competency problems is unclear. This project aims to describe how clinical psychology trainees with PPC are identified and managed within the Australian and New Zealand context. Method: An online survey was distributed through Australian and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
7
0
3
Order By: Relevance
“…Students need to be able to maintain their competence to engage as mental health practitioners and to meet the demands for self-care as required by professional associations. Although many universities in Australia, for example, recommend creating and modelling a culture of self-care for trainees (Perry et al 2017), unfortunately, self-care is not often formally taught or discussed within clinical training programs. In their review of 136 handbooks from clinical psychology doctoral programs, Bamonti et al (2014) found that only 8.4% of general psychology handbooks and 24.8% of clinical psychology handbooks included a reference to self-care, and that they primarily informed already impaired students about services available.…”
Section: Discussionmentioning
confidence: 99%
“…Students need to be able to maintain their competence to engage as mental health practitioners and to meet the demands for self-care as required by professional associations. Although many universities in Australia, for example, recommend creating and modelling a culture of self-care for trainees (Perry et al 2017), unfortunately, self-care is not often formally taught or discussed within clinical training programs. In their review of 136 handbooks from clinical psychology doctoral programs, Bamonti et al (2014) found that only 8.4% of general psychology handbooks and 24.8% of clinical psychology handbooks included a reference to self-care, and that they primarily informed already impaired students about services available.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and reliable measurement of early supervision and trainee competence is crucial to the objective evaluation of specific competencies and trainee performance (Gonsalvez & McLeod, 2008;Gonsalvez, Oades, & Freestone, 2002;Nicholson-Perry, Donovan, Knight, & Shires, 2017;Rodolfa et al, 2014;von Treuer & Reynolds, 2017). Further to this, comparison of supervisor and supervisee perceptions of supervision to determine which factors contribute to concordance and discordance in supervisory dyads regarding competency ratings and learning outcomes would be useful.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…A major challenge for professors is the ability to design valid assessment methods that really measure students' higher order thinking skills, which are described in undergraduate psychology programs' graduate profiles, and included in professional standards of different countries (Australian Psychological Society, 2013;Markle, 2017, Oliveri & Markle, 2017. Such assessments need to be ecologically valid, clearly reflecting the content and context of professional practice, while requiring the demonstration of complex thinking skills (Falchikov, 2004;Nicholson Perry, Donovan, Knight, & Shires, 2017).…”
Section: Introductionmentioning
confidence: 99%